PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ANDROID DI SEKOLAH DASAR PERIODE 2020-2024 - Abdul Malik; Yeri Sutopo; Agus Yuwono; Bambang Subali; Nuni Widiarti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Teachers must be able to develop learning media that are relevant to the times and cognitive development of students. The purpose of this research is to see how android-based learning media is developed and implemented in elementary school learning and how feasible the media is after going through the validation test. This research uses the literature review research method which is part of the qualitative method. This research was conduct by reviewing articles from Google Scholar using Publish or Perish using the keywords “Android-Based Learning Media Development”, the period 2020-2024, the type of journal publication, and with 100 search results which were then selected and resulted in 6 articles that were included in the focus and research criteria. The research concluded that android-based learning media can be developed using three research and development models which are ADDIE, DDDD, and Borg & Gall. The percentage of research and and development models used is ADDIE (50%), DDDD (33%), and Borg & Gall (17%). Based on the review of all articles, it is concluded that the android-based learning media that were developed are feasible to be implemented in the teaching and learning process in elementary schools.